Nilai Pendidikan Karakter Kerja Keras dalam Novel Tentang Kamu Karya Tere Liye - Sulastri, Saptiana; Hariyadi, -; Simarmata, Mai Yuliastri (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2020)
This study aims to describe the value of hard work character education in the novel About You Work Tere Liye. Research using descriptive methods with qualitative forms. data collection techniques using documentary studies. Data collection tool in this study is the researcher himself as a key instrument (human instrument) assisted with other data collection tools namely data recording cards. Data analysis techniques in this study used content study techniques. Based on the analysis, the value of hard work character education includes hard work in the family, hard work for yourself, and hard work in working.